Short Selling Around News in International Stock Markets - Gorbenko, Arseny (The Review of Asset Pricing Studies, 2026)
Abstract This paper examines global sources of short sellers’ informational advantage by analyzing their trading around public news releases in 38 countries. I find that shorts on negative news have stronger predictive power than nonnews shorts, but only in countries with high-quality public information, more news per stock, and higher illiquidity. These results indicate that some country-level factors discourage short sellers from trading on public information. Short sellers’ informational advantage in most countries seems to arise from their access to private information, as evidenced by their ability to anticipate future negative news and their trading in unison with insiders. (JEL: G12, G14, G15)